Let's do some calculus! (39)

Calculus Level 5

0 2 Li 3 ( 4 x ) d x \large \displaystyle \int_0^2 \text{Li}_3 (4^x) \, dx

Given the definite integral above, if its value can be represented in the closed form as

a b log b ( Li c ( d ) ζ ( c ) ) \dfrac{a}{b \log b} \bigg( \text{Li}_c (d) - \zeta (c) \bigg)

Find a + b + c + d a+b+c+d .

Notations:

  • Li n ( a ) \text{Li}_n (a) denotes the polylogarithm function , that is Li n ( a ) = k = 1 a k k n \text{Li}_n (a) = \displaystyle \sum_{k=1}^{\infty} \dfrac{a^k}{k^n} .
  • ζ ( s ) \zeta (s) represents the Riemann zeta function , that is ζ ( s ) = n = 1 1 n s \zeta (s) = \displaystyle \sum_{n=1}^{\infty} \dfrac{1}{n^s} .
  • log ( ) \log (\cdot) denotes the natural logarithm function , that is log e ( ) \log_{e}{(\cdot)} or ln ( ) \ln(\cdot) .

Inspired by Hummus A .

For more problems on calculus, click here .


The answer is 23.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tapas Mazumdar
Oct 14, 2016

0 2 Li 3 ( 4 x ) d x = 0 2 k = 1 4 k x k 3 d x = k = 1 1 k 3 0 2 4 k x d x = k = 1 1 k 3 [ 4 k x k log 4 ] 0 2 = k = 1 1 k 4 4 2 k 1 log 4 = 1 log 4 k = 1 4 2 k 1 k 4 = 1 2 log 2 k = 1 ( 1 6 k k 4 1 k 4 ) = 1 2 log 2 ( k = 1 1 6 k k 4 k = 1 1 k 4 ) = 1 2 log 2 ( Li 4 ( 16 ) ζ ( 4 ) ) \begin{aligned} \displaystyle \int_0^2 \text{Li}_3 (4^x) \, dx &= \displaystyle \int_0^2 \sum_{k=1}^{\infty} \dfrac{4^{kx}}{k^3} \, dx \\ &= \displaystyle \sum_{k=1}^{\infty} \dfrac{1}{k^3} \int_0^2 4^{kx} \, dx \\ &= \displaystyle \sum_{k=1}^{\infty} \dfrac{1}{k^3} \left[ \dfrac{4^{kx}}{k \log 4} \right]^2_0 \\ &= \displaystyle \sum_{k=1}^{\infty} \dfrac{1}{k^4} \cdot \dfrac{4^{2k}-1}{\log 4} \\ &= \dfrac{1}{\log 4} \cdot \displaystyle \sum_{k=1}^{\infty} \dfrac{4^{2k}-1}{k^4} \\ &= \dfrac{1}{2 \log 2} \cdot \displaystyle \sum_{k=1}^{\infty} \bigg( \dfrac{16^k}{k^4} - \dfrac{1}{k^4} \bigg) \\ &= \dfrac{1}{2 \log 2} \bigg( \displaystyle \sum_{k=1}^{\infty} \dfrac{16^k}{k^4} - \displaystyle \sum_{k=1}^{\infty} \dfrac{1}{k^4} \bigg) \\ &= \dfrac{1}{2 \log 2} \bigg( \text{Li}_4 (16) - \zeta (4) \bigg) \end{aligned}

Thus

( a , b , c , d ) = ( 1 , 2 , 4 , 16 ) (a,b,c,d) = (1,2,4,16)

Which gives

a + b + c + d = 23 a+b+c+d = \boxed{23}

This has a right approach. However, there is some gap that needs addressing:

The part which needs justifying (even though it's fairly obvious) is why we can interchange the order of the sum/integral in the second step in your working?

Pi Han Goh - 4 years, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...